2006
DOI: 10.1111/j.1439-0329.2006.00444.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation of heartrot, sapwood infection and polyphenol extractives with provenance of Acacia mangium

Abstract: Infection of heartwood by decay fungi (heartrot) is a concern for growers of Acacia mangium for solidwood products as the incidence can be high in some regions of Indonesia. Variation of heartrot incidence for different provenances of A. mangium was determined using two field trials in Sumatra, Indonesia. In a Riau Province trial of 21 provenances, the effect of provenance was statistically significant for natural heartrot incidence, which ranged from 1.6% to 27.2%. In a smaller trial using artificial inoculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Phenolic Cp2, identified as 2,3‐trans 3,4′,7,8 tetrahydroxyflavanone, has been previously recorded at significantly higher levels in the heartwood of A. auriculiformis compared to A. mangium (Barry et al., , ; Mihara et al., ). This compound showed antifungal activity against Phellinus noxius and P. badius using in vitro bioassays (Mihara et al., ), and it was suggested that it accounted for the lower susceptibility of A. auriculiformis to heart rot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic Cp2, identified as 2,3‐trans 3,4′,7,8 tetrahydroxyflavanone, has been previously recorded at significantly higher levels in the heartwood of A. auriculiformis compared to A. mangium (Barry et al., , ; Mihara et al., ). This compound showed antifungal activity against Phellinus noxius and P. badius using in vitro bioassays (Mihara et al., ), and it was suggested that it accounted for the lower susceptibility of A. auriculiformis to heart rot.…”
Section: Discussionmentioning
confidence: 99%
“…Phenolic compounds such as stilbenes, flavonoids, lignans and tannins have been shown to play a major role in tree defence following fungal invasion in some woody plants (Eyles, Bonello, Ganley, & Mohammed, ; Eyles, Davies, & Mohammed, ; Eyles, Davies, Yuan and Mohammed ; Pearce, ; Wallis et al., ; Woodward, Bianchi, Bodles, Beckett, & Michelozzi, ). The phenolic chemistry of A. auriculiformis and A. mangium heartwood has been examined previously; however, these studies focused on heartwood extractives (Barry, Mihara, Davies, Mitsunaga, & Mohammed, ; Barry et al., ; Mihara, Barry, Mohammed, & Mitsunaga, ). In functional sapwood, infection is restricted by inducible defence mechanisms including de novo accumulation of polyphenols and changes in water content; in contrast, heartwood, comprising of dead cells, rely on high levels of extractives to restrict fungal colonisation (Pearce, ).…”
Section: Introductionmentioning
confidence: 99%
“…The fact that this is an ex-grassland site may also contribute to the low incidence of heart rot as lower abundance and diversity of wood-rotting fungi are present in these plantations compared to those established on ex-forest sites (Risna and Suhirman, 2003). In an A. mangium provenance trial conducted in South Sumatra, Subanjeriji plus trees (similar seed stock to that planted in this trial) were assessed for heart rot and were found to have the second lowest incidence of heartwood infection associated with drill wounds of a total of six provenances (Barry et al, 2006). Therefore, site factors and provenance may explain the lack of heart rot detected in the pruning trial.…”
Section: Heart Rotmentioning
confidence: 97%
“…In addition, while singling wounds are typically assumed to have a large impact on heart rot establishment, an influence of singling in a provenance trial in the Riau province of Sumatra was not apparent (Barry et al, 2006).…”
Section: Heart Rotmentioning
confidence: 99%
“…Such physical barriers can significantly confine the advancement of fungal infection in different woody hosts (Robinson & Morrison 2001;Robinson et al 2004). In addition, there are indications that activation and accumulation of different chemical barriers such as phytoalexins and pathogenesis-related proteins during hostpathogen interactions can inhibit fungal spread (Barry et al 2006;Sturrock et al 2007;Freeman & Beattie 2008;Kovalchuk et al 2013). Secretions of sap or resin which may also restrict fungal spread (Kovalchuk et al 2013) were also observed in this study following stem wounding and inoculation with different Botryosphaeriaceae fungi under glasshouse and field conditions .…”
Section: Major Findingsmentioning
confidence: 99%